Synthesis and characterisation of mesoporous hybrid silica-polyoxometalate aerogels for photocatalytic degradation of rhodamine B and methylene blue. Issue 14 (14th November 2019) - Yahya, Fatima; El-Rassy, Houssam; Younes, Ghassan; Al-Oweini, Rami
ABSTRACT: Mesoporous silica aerogel/polyoxometalate hybrids were successfully synthesised under mild conditions, and were investigated towards photocatalytic degradation of Rhodamine B and Methylene Blue dye models in aqueous media under ultraviolet irradiation. The materials were characterised, in the solid state, by various tools such as FTIR, TGA, and powder XRD, in order to gather information about their chemical and structural properties. Moreover, UV-Vis, AAS, BET, SEM, and EDX techniques were used to confirm the polyoxometalates' loading and their distribution onto the silica aerogels' surface. The most important analytical technique was the Nitrogen adsorption-desorption, which revealed a significant increase in the specific surface area and pore volume of the hybrid catalysts after immobilisation. The synthesised hybrid catalysts, TEOS/PW12 and TEOS/SiW12, have shown efficient photocatalytic activity towards Methylene Blue and Rhodamine B degradation within 120 min under ultraviolet illumination, thus reaching a degradation percentage of 81–98% and 55–90%, respectively. UV-Vis analysis was employed to scrutinise the formation of intermediate species and revealed that the photocatalytic degradation process proceeded to completion within a surprisingly short time of 5 min.